Host plant phylogeny and abundance predict root‐associated fungal community composition and diversity of mutualists and pathogens. (12th April 2019) - Schroeder, John W.; Martin, Jessica T.; Angulo, Diego F.; Arias‐Del Razo, Itzel; Barbosa, Jomar M.; Perea, Ramón; Sebastián‐González, Esther; Dirzo, Rodolfo
Abstract: Interactions between plants and their root‐associated fungi (RAF) may influence the relative abundance of tree species and determine forest community diversity. Such plant–soil feedbacks in turn depend on the degree to which spatial distance and phylogenetic relatedness of host trees structure pathogen and mutualist communities, but research detailing these aspects of RAF communities is lacking. Here, we characterize plant–RAF associations across a diverse plant community, focusing on the degree to which RAF communities are structured by spatial distance, host phylogenetic relatedness, and host abundance. We compare results for different functional groups, including both putative mutualists and pathogens, an aspect poorly examined hitherto. We collected roots at regular intervals along ten 50 m by 2 m transects, then used DNA barcoding to identify host plants, and characterize the associated fungal community. Variance partitioning was used to measure the relative contributions of host phylogenetic relatedness and spatial distance to explaining RAF community composition. A weighted linear regression was used to measure the correlation between host abundance and RAF diversity. Phylogenetic distance among hosts was a better predictor of RAF community composition than spatial distance, but this relationship was stronger for putative pathogens than for mutualists, suggesting that pathogens show stronger host preference than mutualists. Across all functional groups, RAF showed similar levels of spatial structure. Additionally, RAF communities of locally abundant plants were less diverse than RAF communities of rare plants. Synthesis . We found that RAF communities are structured by the phylogenetic relatedness of hosts and, to a lesser extent, by spatial distance, with pathogens showing stronger host preference than mutualists. Abundant hosts had less diverse RAF communities than rare hosts, which is notable because abundant plants tend to experience weaker negative plant–soil feedback. Going forward, mechanisms underlying the host abundance‐RAF diversity relationship warrant further investigation. Additionally, the survey approach presented here could be paired with experiments linking RAF community composition to plant recruitment. Abstract : We found that RAF communities are structured by the phylogenetic relatedness of hosts and, to a lesser extent, by spatial distance, with pathogens showing stronger host preference than mutualists. Abundant hosts had less diverse RAF communities than rare hosts, which is notable because abundant plants tend to experience weaker negative plant–soil feedback. Going forward, mechanisms underlying the host abundance‐RAF diversity relationship warrant further investigation. Additionally, the survey approach presented here could be paired with experiments linking RAF community composition to plant recruitment. RESUMEN: Las interacciones entre plantas y hongos asociados a las raíces (RAF) pueden tener influencia en la abundancia relativa de las especies de árboles y determinar la diversidad de bosques a través de retroalimentaciones planta‐suelo. Estas, a su vez, dependen del grado en que la distancia física y la relación filogenética de los árboles hospederos estructuran las comunidades de patógenos y mutualistas. Sin embargo, estos aspectos de la ecología de las comunidades RAF han sido muy poco examinados. Aquí caracterizamos las asociaciones entre plantas y RAF en una comunidad vegetal diversa, centrándonos en el grado en que las comunidades RAF están estructuradas por la distancia física, y la relación filogenética y abundancia del hospedero. Además, comparamos los resultados considerando diferentes grupos funcionales, incluyendo mutualistas y patógenos putativos, un aspecto poco examinado hasta ahora. Recolectamos raíces a intervalos regulares a lo largo de diez transectos (50 m por 2 m), usamos códigos de barras de ADN para identificar las plantas hospederas y caracterizar la comunidad RAF. Utilizando métodos de repartición de la varianza medimos las contribuciones relativas de la relación filogenética del hospedero y de la distancia física para explicar la composición de la comunidad RAF. Mediante una regresión lineal ponderada medimos la correlación entre la abundancia del hospedero y la diversidad de RAF. La distancia filogenética entre los hospederos fue un mejor predictor de la composición de la comunidad RAF que la distancia física, pero esta relación fue más fuerte para los patógenos putativos que para los mutualistas. Esto sugiere que los hongos patógenos muestran una preferencia más fuerte por el hospedero que los mutualistas. En todos los grupos funcionales, RAF mostró niveles similares de estructura espacial. Además, las comunidades RAF de plantas localmente abundantes fueron menos diversas que las comunidades RAF de plantas raras. Síntesis: Las comunidades de RAF están estructuradas predominantemente por la relación filogenética de los hospederos y, en menor medida, por la distancia física, donde los patógenos muestran una preferencia de hospedero más fuerte que los mutualistas. Los hospederos abundantes albergan comunidades RAF menos diversas que los hospederos raros, lo cual es notable porque las plantas abundantes tienden a experimentar una retroalimentación negativa planta‐suelo más débil. Sin duda, los mecanismos subyacentes a la relación entre la diversidad de RAF y la abundancia del hospedero merecen investigación adicional. Además, proponemos que protocolos de muestreo como el aquí presentado podrían combinarse con experimentos que vinculen la composición de la comunidad RAF con el reclutamiento de plantas.